Pengolahan Bekatul dan Spirulina Menjadi Cookies Kaya Protein - Diki Danar Tri Winanti; Susilawati Susilawati; Zulferiyenni Zulferiyenni (The University of Lampung, 2021)
The rice bran and spirulina are Indonesia's local product that have high nutritional content. Their postharvest with processed it to cookie hoped to enhance diversification of rice bran and spirulina in order to increase people's nutritional intake. The purpose of the study was to study the postharvest of rice bran and spirulina to cookies with rich of protein. This research used Completely Randomized Design (CRD) method and the advanced test Duncan Multiple Range Test (DMRT) with four treatments of cookies was 13.3%, 11.1%, 8.8%, and 6.6% rice bran. The analysis used proximate tests (water content, proteins, fat, and ash) and hedonically sensory tests (color score, aroma, taste, texture, and overall acceptance). The best cookies were 11,1% concentration of rice bran. Their chemical properties were 3.34% water content, 7.26% protein, 37.2% fat, and 47.01% carbohydrates that have filled up the National Standart of Indonesia (SNI) of biscuits whereas ash content 4.31% exceeds the maximum limit. The sensory characteristics of coockie was neutral color, neutral aroma, rather fond taste, liking texture, and overall like. Keywords: cookies, rice bran, sensory test, spirulina